The mediating role of transformational leadership and perceived use of artificial intelligence in the effect of happiness on innovative work behavior - Aji Pangestu Sujatmiko; Akhmad Darmawan; Hermin Endratno; Restu Frida Utami (Journal of Management Small and Medium Enterprises (SMEs), 2026)
Innovative work behavior among medical personnel is a critical factor in improving the quality of hospital health services, as it contributes to work effectiveness and service excellence. This study aims to examine the effect of happiness on innovative work behavior, with transformational leadership and perceived use of artificial intelligence (AI) as mediating variables among medical staff. The research population comprises all medical personnel at RS Islam Purwokerto, with purposive sampling employed to obtain 184 respondents as the study sample. The study applies SEM-PLS analysis using SmartPLS 4.0 and adopts Social Exchange Theory as the theoretical framework for explaining the relationships among variables. The findings indicate that happiness has a positive and significant effect on innovative work behavior, both directly and indirectly through the mediation of perceived AI use. However, transformational leadership is not proven to mediate the effect of happiness on innovative work behavior. This study highlights the importance for hospitals to foster a work environment that supports the psychological well-being of medical personnel and to optimize positive perceptions of AI use through appropriate training and governance in order to effectively support innovation. Keywords: Happiness; Transformational Leadership; Innovative Work Behavior; Perceived Use of Artificial Intelligence